Estimation of heterosis, combining ability and reciprocal effects for body weight in four genetic groups of chicken from a full diallel cross - Teshome, Philimon; Goshu, G.; Esatu, Wondmeneh; Dessie, Tadelle (Elsevier, 2025)
This study aims to estimate the heterotic effects (He), general combining abilities (GCA), specific combining abilities (SCA), and reciprocal effects (RE) for body weight (BW) in a 4 × 4 full diallel cross involving Improved Horro (H), commercial Sasso (S), Potchefstroom Koekoek (K), and Dz-white feathered (D) chickens. A total of 960 purebred and F1 hybrid chickens were used in this study, comprising sixteen genetic groups. The birds were reared from hatch to 14 weeks (wk) of age in a deep litter floor house partitioned with wire mesh. Chickens of different genotypes were randomly assigned to three pens per genetic group in a completely randomized design. BW measurements were recorded at hatch, 2, 4, 6, 8, 10, 12, and 14 wk of age. Heterosis estimates indicated that crosses between S males with K and D females (including their reciprocal crosses) exhibited the strongest He for BW from early to late ages. In contrast, crosses between H males and K females (and their reciprocals) showed positive but low He, which increased slightly at later ages. Meanwhile, the cross between K males and D females displayed negative He across all ages, whereas its reciprocal cross had low but positive He. GCA effects were high (p < 0.0001) among purebreds, which shows the importance of additive gene effects on BW. SCA highly (p < 0.0001) influenced BW at hatch, wk 2, 4, and 10, highlighting the role of non-additive genetic variance at the early age of BW inheritance. RE was generally non-significant except at hatch (p = 0.002), wk 2 (p < 0.0001), and wk 10 (p = 0.036), indicating potential maternal or paternal contributions during these early developmental stages. In conclusion, the results indicated that breeding strategies should prioritize selecting parents with superior GCA to ensure consistent and predictable gains in BW. Furthermore, developing a broiler line from S sires crossed with the K and D dams and H sires with S dam lines should also be considered.